Bonsoir CR7101
[tex]C=x(4-6x)+3x-9[/tex]
1) Développer et réduire :
[tex]C=x(4-6x)+3x-9\\\\C=4x-6x^2+3x-9\\\\\boxed{C=-6x^2+7x-9}[/tex]
2) Tester la réponse
a) pour x = 0.
[tex]C=x(4-6x)+3x-9\\C=0(4-6\times0)+3\times0-9\\C=0+0-9\\C=-9[/tex]
[tex]C=-6x^2+7x-9\\C=-6\times0^2+7\times0-9\\C=0+0-9\\C=-9[/tex]
Les valeurs finales sont égales.
b) pour x = 1.
[tex]C=x(4-6x)+3x-9\\C=1(4-6\times1)+3\times1-9\\C=(4-6)+3-9\\C=-2+3-9\\C=-8[/tex]
[tex]C=-6x^2+7x-9\\C=-6\times1^2+7\times1-9\\C=-6+7-9\\C=-8[/tex]
Les valeurs finales sont égales.